Vaccinia virus-mediated cancer immunotherapy: cancer vaccines and oncolytics. Issue 1 (9th January 2019) - Guo, Zong Sheng; Lu, Binfeng; Guo, Zongbi; Giehl, Esther; Feist, Mathilde; Dai, Enyong; Liu, Weilin; Storkus, Walter J.; He, Yukai; Liu, Zuqiang; Bartlett, David L.
Abstract : Cancer vaccines and oncolytic immunotherapy are promising treatment strategies with potential to provide greater clinical benefit to patients with advanced-stage cancer. In particular, recombinant vaccinia viruses (VV) hold great promise as interventional agents. In this article, we first summarize the current understanding of virus biology and viral genes involved in host-virus interactions to further improve the utility of these agents in therapeutic applications. We then discuss recent findings from basic and clinical studies using VV as cancer vaccines and oncolytic immunotherapies. Despite encouraging results gleaned from translational studies in animal models, clinical trials implementing VV vectors alone as cancer vaccines have yielded largely disappointing results. However, the combination of VV vaccines with alternate forms of standard therapies has resulted in superior clinical efficacy. For instance, combination regimens using TG4010 (MVA-MUC1-IL2) with first-line chemotherapy in advanced-stage non-small cell lung cancer or combining PANVAC with docetaxel in the setting of metastatic breast cancer have clearly provided enhanced clinical benefits to patients. Another novel cancer vaccine approach is to stimulate anti-tumor immunity via STING activation in Batf3-dependent dendritic cells (DC) through the use of replication-attenuated VV vectors. Oncolytic VVs have now been engineered for improved safety and superior therapeutic efficacy by arming them with immune-stimulatory genes or pro-apoptotic molecules to facilitate tumor immunogenic cell death, leading to enhanced DC-mediated cross-priming of T cells recognizing tumor antigens, including neoantigens. Encouraging translational and early phase clinical results with Pexa-Vec have matured into an ongoing global phase III trial for patients with hepatocellular carcinoma. Combinatorial approaches, most notably those using immune checkpoint blockade, have produced exciting pre-clinical results and warrant the development of innovative clinical studies. Finally, we discuss major hurdles that remain in the field and offer some perspectives regarding the development of next generation VV vectors for use as cancer therapeutics.